Holistic and inquiry-based teaching of sustainable chemistry - Juntunen, Marianne (LUMAT-B: International Journal on Math, Science and Technology Education, 2016)
The most important function of the branch of chemistry and teaching is to promote sustainable development. This article discusses central viewpoints of the teaching of sustainable chemistry. This article is based on a doctoral dissertation, where such information is the starting point: we will encounter great challenges connected to the viability of the earth, to our health and peace in the near future at the latest. Our students are the future citizens in preventing and solving these challenges. Chemistry teaching may strengthen the necessary civics, because chemistry as a branch of science is in a great role in the development of the world. In addition to environmental conscious teachers, chemists committed to sustainable development are needed. Sustainable development and augmentation towards ethical responsibility is emphasized widely – in the Finnish National Core Curriculum for Basic Education, in national and international teaching strategies, in the research literature of chemistry teaching and in the chemical industry. The problem is the fact that handling of topics of sustainable development completely and experimentally is still quite concise in the teaching of chemistry. In this article, examples for studying a topic in chemistry teaching are introduced.